Framing Risk and Social Norms: Effective Communication Strategies to Increase COVID-19 Vaccine Uptake - Vanie, Adevy; Hariyanti, Anggelina (Indonesian Scientific Publication, 2024)
Effective communication strategies are essential to combat vaccine hesitancy and enhance public health outcomes, particularly during global health crises such as the COVID-19 pandemic. This study investigates the impact of various communication framings educational, loss vs. gain framing, and social normative appeals on COVID-19 vaccine uptake. The objective is to identify strategies that are psychologically and culturally attuned to diverse populations. Using a systematic review and meta-analysis of 49 randomized controlled trials (RCTs), alongside case studies from China and the UK, this study evaluates the effectiveness of message types in promoting vaccine acceptance. Data were synthesized using fixed- and random-effects models, and subgroup analysis was conducted based on framing strategy and psychological orientation. Results show that loss-framed and normative messages significantly outperform gain-framed or generic formats. Educational messages produced pooled risk ratios (RRs) of 1.23–1.28, while loss-framed messages achieved an RR of 1.45. Case studies highlighted that individual framing works better for audiences with low institutional trust, whereas community framing is more effective in collectivist cultures and among those with strong just-world beliefs. Message effectiveness also varied by education level and cultural context. These results underscore the importance of tailored, psychologically informed, and culturally contextualized communication. The study contributes a nuanced framework for vaccine promotion based on behavioral science and highlights the need for adaptive, inclusive public health messaging in future crises.